Identifying factors key to encouraging entrepreneurial intentions among seniors. (December 2015) - Sahut, Jean‐Michel; Gharbi, Sami; Mili, Mehdi
Abstract: Using the theory of planned behaviour (TPB), we examined the impact of age on entrepreneurial intention, with special focus on seniors. Using samples from France reflecting a broad age range, a negative relationship involving age and entrepreneurial intent was found. Consistent with TPB, attitude, social norms, and perceived behavioural control were all significantly associated with intent. Importantly however, the relative weight seniors gave these components differed from that of prime age participants. For seniors, the belief that they had the requisite competencies and resources needed to own a business was especially important. Seniors also expressed greater relative interest in social entrepreneurship. The implications of these findings for both researchers and public policy makers are considered. Copyright © 2015 ASAC. Published by John Wiley & Sons, Ltd.